Analisis dan Perancangan Sistem Informasi Penyaluran Dana Zakat berbasis Web menggunakan Framework Laravel: Studi Kasus di Yayasan Baitul Maal PLN Depok - Munir, Sirojul; Surya, Tubagus Muhammad Billal Zakky (LPPM STT Terpadu Nurul Fikri, 2024)
The Baitul Maal PLN Depok Foundation is one of the national amil zakat institutions that currently, in its administrative management of YBM PLN, is still using the manual method, namely by receiving the submission file and determining the time so that it can discuss with the management of YBM PLN then a decision is made from the results of the discussion. This method takes a long time because an amil receiving the application file must wait for free time from the PLN YBM management. In building this system, the stages of data collection were carried out with literature studies and field studies. The system design and development phases used Unified Modeling Language diagramming and Extreme Programming development models. Based on the results of black box testing of application functionality, the percentage of success is 100%. For the UAT test, the results were 100% on the super admin side, 100% on the admin side, 100% on the mail side, and 100% on the employee side. Meanwhile, from the questionnaire given to 10 respondents regarding the feasibility of the application, the results were 75%. The conclusion is that the application to distribute Zakat funds is sufficient to facilitate YBM PLN's decisions on applications received.